Analisis Motivasi Berwirausaha pada Mahasiswa Universitas Medika Suherman - Rico Septia B.; Nurhasan Nurhasan (J-MAS (Jurnal Manajemen dan Sains), 2023)
This research aims to analyze how much motivation students have towards entrepreneurship and find out what factors are related to and influence motivation towards entrepreneurship among students. The method used in this study is a quantitative analysis method using primary data. The primary data was obtained from data collection by distributing questionnaires with a total sample of 120 students. Data analysis techniques in this study used instrument and classic assumption test, descriptive analysis, factor analysis, and multivariate analysis. The results of the descriptive analysis show that the empirical mean value is greater than the theoretical mean value for each variable (50.60 > 39), so descriptive analysis can interpret that the entrepreneurial motivation of Suherman Medika University students tends to be good. Furthermore, the results of the factor analysis in this study obtained a Kaiser Meyer Olkin Measure of Sampling Adequacy (KMO MSA) value of 0.661 > 0.50 and Bartlett's Test of Sphericity value of 0.000 <0.05, which means that the variables referred to in this study did not correlate with one another in the population. In addition, based on factor analysis found that self-efficacy, attitudes and social support are factors that influence entrepreneurial motivation. Then, the results of the multivariate test show that the significance value for Pillai's trace, Wilk's lambda, Hotelling trace, and Rpy's largest root is less than 0, which means that there is a partial effect on self-efficacy, attitudes, and social support on entrepreneurial motivation. Based on multivariate testing, it shows that the value of the self-efficacy determination coefficient is 0.740, Attitude determination coefficient value of 0.811, and the value of the Social Support determination coefficient is 0.536. Based on the results of this study, it is hoped that later both institutions, student organizations and the campus environment will be able to facilitate student needs better.